Characteristics of Cement Mortar with M-sand as Replacement of Fine Aggregates. (2018) - Radhakrishna,; Praveen Kumar, K.
Abstract: Natural sand obtained from river bed is conventionally used as fine aggregates in preparation of cement mortar. Present study investigates flow and strength characteristics of cement mortar at various replacement levels of alternative fine aggregate, M-sand. Plastering mortars (1:3 and 1:4 ratio) were prepared with natural sand as fine aggregates. Flow characteristics of the mortar was studied by conducting flow test to attain flow of 110% for plastering mortar. Natural sand was replaced by M-sand at levels of 20, 40, 60, 80, and 100%. Flow test was conducted on all mortars and the effect of M-sand replacement on flow characteristics was studied. Cubes were cast, cured and tested to evaluate the effect of M-sand replacement on mortar compressive strength at age of 7, 14, 28 and 56 days. Modulus of elasticity was evaluated by casting and testing mortar prisms. Results indicate that water cement ratio required to attain flow of 110% in plastering mortar decreases with increase in M-sand percentage. As expected, the compressive strength of mortar decreases with increase in water cement ratio. Also increase in compressive strength was observed with increase in percentage of M-sand. Increased modulus of elasticity were observed in M-sand mortar when compared to natural sand.